The Ypresian ichthyofauna of the Monte Solane Lagerstätte (Verona, northern Italy): A deep dive into the western Tethys early Eocene mesopelagic setting - Pietro Calzoni; Luca Giusberti; Eliana Fornaciari; Valeria Luciani; Flavia Boscolo-Galazzo; Massimo Bernardi; Riccardo Tomasoni; Giorgio Carnevale (PLoS ONE, 2026)
The Ypresian (lower Eocene) fish-bearing site of Monte Solane (Verona province, northern Italy) was discovered in the early 2000s, and its stratigraphy was thoroughly investigated more than a decade ago. However, its ichthyofauna, largely dominated by mesopelagic bony fishes, remained largely unstudied, even though it represents the second richest assemblage in the Verona province, ranking immediately after the Bolca Lagerstätten , which are globally renowned for their exceptionally abundant and diverse reef-associated fish assemblages. The scientific relevance of Monte Solane resides in being, along with the Solteri Lagerstätte (Trento province, northern Italy), the nearly coeval bathyal equivalent of Bolca. The Monte Solane ichthyofauna, represented by almost 200 collected specimens, comprises what reflects a mesopelagic assemblage including stomiiforms (Gonostomatidae and Phosichthyidae), myctophiforms (Myctophidae), and various percomorphs (Euzaphlegidae, Gempylidae, and Trichiuridae), plus a few more groups usually linked to the coastal epipelagic or benthic habitats (e.g., Clupeiformes and Apogonidae). Several new taxa are established herein: Acanthophleges lessiniae n. gen. et n. sp., Bolcaichthys solanensis n. sp., Contemptor mastinoi n. gen. et n. sp., Eomastix zabimaru n. gen. et n. sp., Lepidoclupea renga n. gen. et n. sp., Sabbathichthys osbournei n. gen. et n. sp., Thyrsitoides cangrandei n. sp., and Veronaphleges ambrosii n. sp. The stratigraphic relationships of the Monte Solane and Solteri sections are also investigated, and their assemblages are compared to better understand the main features of the Eocene mesopelagic environments of the western part of the Tethys. Exploring these sites can help to unveil the paleontological characters of the most ancient known Cenozoic deep-water Lagerstätten known, and also to better define the structure of the pelagic fish communities during the demise of the Early Eocene Climatic Optimum (EECO; ~ 53.2–49.1 Ma), the interval of the Cenozoic with the warmest long-term global average temperature and highest CO 2 levels.